Knowledge, attitude and practice of blood donation among students in UiTM Puncak Alam / Azeefarleena Ali, Muhammad A'fifi Fazil, Noor Maizurah Abd Lateef - Ali, Azeefarleena; Fazil, Muhammad A'fifi; Abd Lateef, Noor Maizurah (2016)
Introduction: Blood donation is considered as a social responsibility involving community. Youth comprised of 65.4% from Malaysian population and university students contributed a huge part as blood donors. Aim of study: The aim of the study is to assess the knowledge, attitude and practice on blood donation among undergraduate students in Universiti Teknologi MARA Puncak Alam. Methodology: A descriptive cross-sectional study of 418 respondents using selfadministered questionnaire adapted from previous study. Results: 31.8% (133/418) of respondents found to have good knowledge, 83.3% (348/418) of respondents showed positive attitude towards blood donation and 32.1% (134/418) of respondents had donated blood previously. There was significant difference in knowledge, attitude and practice between health programs and non-health programs students (p<0.05). Health programs students has better knowledge on blood donation (mean rank=238.30, p=0.001), health programs students and students within age range of 19-21 years old has better attitude towards blood donation (mean rank=229.25,p=0.039,mean rank=217.76,p=0.001) and female students, fourth year students and health programs students has better practice on blood donation (mean rank=216.84,p=0.015,mean rank=238.04,p=0.003, mean rank=223.64,p=0.001). Conclusion: This study concludes health programs and non-health programs students differ in knowledge, attitude and practice on blood donation. Motivational support is needed to increase awareness on blood donation among non-health programs students.